Aspects Concerning the Perception of the English Liberalism by the Transylvanian Romanians during the XIXᵗʰ Century - FAUR, Andrei (Studia Universitatis Babeș-Bolyai Historia, 2016)
Constructing Gender in Romanian Proverbs. In Romanian proverbs, the woman is evil, lazy, shrewed, weak, talkative, but she can also be beautiful, diligent, good, honest and still she is not like a man. Anyway she does, the woman stays in a man’s shadow, even if she reaches the superior limits of her abilities, this will only mean the inferior limits of men’s abilities, all these proverbs seem to be transmitting to us through time. They undoubtedly come from a past reality – most of them were gathered and published in collections at the end of 19th century – though it is impossible to find a period of origin. More important is the fact that they prove some valability today and this denotes a too little or no change at all regarding the attituted towards woman and her perception in society. Rezumat: Construirea genului în proverbele româneşti. În proverbele româneşti, femeia este rea, leneşă, vicleană, slabă, guralivă, dar poate să fie şi frumoasă, muncitoare, cuminte, cinstită. Totuşi, ea nu este ca un bărbat. Orice ar face, femeia este mereu în umbra bărbatului. Chiar dacă atinge limita superioară a posibilităţilor sale, aceasta înseamnă de-abia atingerea limitei inferioare a capacităţilor masculine – ne spun toate aceste proverbe. Chiar dacă vin dintr-o realitate trecută, majoritatea fiind culese şi publicate în colecţii de folclor din secolul al XIX-lea, este imposibil să le datăm cu exactitate. Mai important este însă faptul că ele îşi dovedesc valabilitatea şi astăzi, ceea ce denotă o schimbare foarte redusă în ceea ce priveşte atitudinea faţă de femeie şi percepţia ei în societate. Cuvinte-cheie: identitate de gen, discurs masculin, proverbe, epoca modernă, folclor românesc